Nossos passos vêm de longe: Almerinda Farias Gama e o ativismo político de uma mulher negra na construção da luta feminista brasileira - Patrícia Cibele Tenório (Les Cahiers ALHIM)
This article aims at analyzing Almerinda Farias Gama’s fronts of political action. Gama (1899-1999) was a black suffragist and feminist who played a central role in the construction of female political emancipation in Brazil, especially in the 1930s. Brazilian women's political conquests are usually associated with the struggles of a specific group: white suffragists and belonging to wealthy families. The trajectories of women like Almerinda, point to the presence of black women and members of the working class on the stage of the historical events that led to the obtention of women's political rights. With gigantic political energy, Almerinda diversified her activism to beyond the organized movement of women. She led the association proposed by the Ala Moça do Brasil, joined the founding of the Socialist Proletarian Party of Brazil (PSPB), and also turned into a combative activist in the union movement in Rio de Janeiro, in the first years of government of President Getúlio Vargas. Her competence, enthusiasm and capacity to demand from the authorities and groups of power make Almerinda a lighthouse that illuminates the steps of a new generation of Brazilian black women who fight for spots and recognition in the institutional spaces of power.